The Gambaran Penerapan 6 Sasaran Keselamatan Pasien di Rumah Sakit: Studi Literatur - Muhammad Kholillurrahman; Endang Pertiwiwati; Herry Setiawan (Nerspedia, 2023)
Background: Patient safety is the avoidance, prevention and improvement of actions that result in injury by theprocess of health care actions. Implementation of safety goals must be evaluated and monitored at all times in orderto create safe and high quality health care for every patient and medical staff in the hospital. Objective: thedescription of the implementation of 6 patient safety goals in hospitals. Method: This literature review consists often articles identified from four databases in the period 2010-2020 with quantitative and qualitative researchmethods,